The Habits and Hermeneutics of Digital Bible Readers: Comparing Print and Screen Engagement, Comprehension, and Behavior - Dyer, John (Journal of religion, media and digital culture, 2019)
Christians in general and American evangelicals in particular are increasingly using digital media to access Scripture, but it is unclear how this shift is influencing the behaviors they value most: regular reading and in-depth study. Using survey data, assessments of comprehension, and daily reading progress, this study examines how engagement with the Bible varies between print and screens. Results indicated that American evangelicals use a combination of print and digital forms of Scripture based on the kind of engagement they want to carry out (devotional reading, in-depth study, prayer, etc.). The data also suggest readers have lower comprehension when reading the Bible on screens compared to print. Readers using mobile devices are more likely to engage scripture daily than those using printed Bibles, and these effects are more pronounced in male readers than female readers.